Primary closure of the Urinary Bladder, Urethra and Anterior Abdomen of Classical and Cloacal 39 Exstrophy - A Preliminary Experience of Three Consecutive Cases - Mostaque, AK; Huq, MS; Islam, T; Haque, SM; Rahman, MM (Journal of Surgical Sciences, 2013)
A 4 years old female and 1.5 months old male with classical exstrophy and a 2 days old male child with cloacal exstrophy were admitted in Paediatric Surgery Department of Sher-e-Bangla Medical College Hospital (SBMCH), Barisal. The mothers of all children had complaints of protrusion of fleshy mass in lower abdomen from birth. They always remain wet producing smell of urine. The cloacal exstrophy case had a prolapsed ileum that was discharging stool. He had no anus too. All of the cases underwent one stage closure of urinary bladder and urethra and lower abdomen without osteotomy and patient was discharged. After 8 months of first operation the female patient underwent repair of the wound dehiscence. At the time of discharge her urinary bladder capacity was 10 ml and remained dry for 5 minute after manual evacuation. The male patient with classical exstrophy developed urethrocutaneous fistula on 15th post-operative day. The cloacal exstrophy case was discharged with end ileostomy on 10th post-operative day. DOI: http://dx.doi.org/10.3329/jss.v16i1.14447 Journal of Surgical Sciences (2012) Vol. 16 (1) : 39-43